HYPOTHETICAL APPROACHES TO SCAFFOLDING FOR LEARNING OF STUDIO PAINTINGS - Odewumi, Michael Olubunmi (International Journal of Indonesian Education and Teaching (IJIET), 2020)
Painting is a branch of visual arts discipline in Nigeria education and often traced to Paleolithic age.  The study was inspired by the dismal attitude of undergraduate  towards painting and painting media this makes it very important for painting instructors to vary both media and method in painting.  Therefore, Scaffolding serves as a panacea in filling the existing gap.  Quasi-experimental design was used in the study.   60 undergraduate fine arts students of 200 levels of 29 male and 31 female were taken from a Nigeria university.   The study presented two research questions and formulated two null hypotheses at 0.05 level of significance.   Scaffolding Painting Achievement Test (SPAT) was of 50 items objectives question extract from validated JAMB visual arts examination was the test items. The Data collected were analyzed with ANCOVA and t-test.  Study disclosed that undergraduate students taught painting via Scaffolding performed better and no significant difference was recorded between the mean of both female and male arts learners exposed to Scaffolding. It was recommended that Scaffolding should be used for teaching of painting in Nigeria university..  DOI: 10.24071/ijiet.2020.040104